Male genital lichen sclerosus, microincontinence and occlusion: mapping the disease across the prepuce. (18th April 2022) - Kravvas, Georgios; Muneer, Asif; Watchorn, Richard E.; Castiglione, Fabio; Haider, Aiman; Freeman, Alex; Hadway, Paul; Alnajjar, Hussain; Lynch, Magnus; Bunker, Christopher B.
Summary: Background: Male genital lichen sclerosus (MGLSc) can lead to significant sexual dysfunction and urological morbidity, and is also a risk factor for premalignant disease (penile intraepithelial neoplasia and penile cancer), particularly squamous cell carcinoma. Although the precise aetiopathogenesis of MGLSc remains controversial, accumulated evidence indicates that it is related to chronic, intermittent, occluded exposure to urine. Aim: To perform spatial mapping of MGLSc across the human prepuce and assess how this supports the urinary occlusion hypothesis. Methods: Preputial samples were collected from 10 patients with clinically diagnosed MGLSc undergoing circumcision. The samples were then divided into a grid pattern and 10 punch biopsies were obtained from each section to determine the extent and distribution of the disease process across each prepuce. Results: All 10 patients reported having urinary microincontinence, and all were histologically confirmed as having MGLSc. The most proximal aspect of the prepuce was found to be universally affected by MGLSc in all patients, whereas the most distal part was overwhelmingly shown to be the least affected area. Of the 63 MGLSc‐affected regions, 62 were in direct physical contiguity with one another. The histological extent of the disease was not found to be congruent with either the severity of the symptoms reported by the patients or the clinical examination. Conclusion: In uncircumcised men with urinary microincontinence, after the prepuce has been replaced post micturition, small amounts of urine can pool between the juxtaposed epithelial surfaces. The proximal aspect of the prepuce is subjected to the maximum amount of occlusion and maximal contact with accumulated urine, whereas the distal prepuce is subjected to the least. Our findings suggest that accentuated contact between urine and susceptible penile epithelium due to occlusion can lead to MGLSc. Furthermore, contiguity data suggest that once established, it is possible that MGLSc advances across tissues by physical contact. This is the first study examining the changes in the preputial landscape in patients with LSc and contributes to our understanding of disease aetiology and progression. Abstract : We performed mapping biopsies on 10 circumcision samples to determine the extent and distribution of male genital lichen sclerosus (MGLSc) across each prepuce. The proximal parts of the prepuce (where occlusion is favoured) were universally affected by MGLSc, whereas the distal parts of the prepuce (where less occlusion occurs) were markedly less likely to be affected. These findings strongly support the hypothesis that chronic, intermittent and occluded exposure of susceptible epithelium to urine is a key driver for the development of MGLSc.